2011
DOI: 10.1364/oe.19.011415
|View full text |Cite
|
Sign up to set email alerts
|

Harmonic generation in silicon nitride ring resonators

Abstract: We demonstrate second- and third-harmonic generation in a centrosymmetric CMOS-compatible material using ring resonators and integrated optical waveguides. The χ(2) response is induced by using the nanoscale structure of the waveguide to break the bulk symmetry of silicon nitride (Si3N4) with the silicon dioxide (SiO2) cladding. Using a high-Q ring resonator cavity to enhance the efficiency of the process, we detect the second-harmonic output in the visible wavelength range with milliwatt input powers at telec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
257
5
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 302 publications
(276 citation statements)
references
References 24 publications
10
257
5
4
Order By: Relevance
“…Extremely wide-band frequency combs [64 -66], sub 100-GHz combs [67], line-by-line arbitrary optical waveform generation [68], ultrashort pulse generation [15,70], and dual frequency combs [71] have been reported. In addition, OFC harmonic generation [72] has been observed. These breakthroughs have not been possible in SOI at telecom wavelengths because of its low FOM.…”
Section: Introductionmentioning
confidence: 92%
“…Extremely wide-band frequency combs [64 -66], sub 100-GHz combs [67], line-by-line arbitrary optical waveform generation [68], ultrashort pulse generation [15,70], and dual frequency combs [71] have been reported. In addition, OFC harmonic generation [72] has been observed. These breakthroughs have not been possible in SOI at telecom wavelengths because of its low FOM.…”
Section: Introductionmentioning
confidence: 92%
“…Second order optical nonlinearity (χ (2) ) is one of the most widely explored properties in photonics, utilizing various nonlinear materials [8][9][10][11][12][13]. χ (2) nonlinearity enables the coupling between photons with very different colors, acting as the basis for many important applications such as second harmonic generation, spontaneous parametric down conversion, optical parametric amplification and oscillation.…”
mentioning
confidence: 99%
“…In silicon, however, SHG cannot be directly excited, because the second-order susceptibility vanishes in this material, as a result of the crystal centro-symmetry. Exploitation of silicon nitride (Si 3 N 4 ) has been proposed to solve this drawback and induces second-order nonlinear processes in silicon compatible structures [17][18][19][20]. More recently, Oliveira et al reported SHG in a 20 mm radius Si 3 N 4 ring resonator by using the electric field induced SHG process and calculated a conversion efficiency of about 3.68 £ 10 ¡3 with a pumping power of 75 mw [19].…”
Section: Introductionmentioning
confidence: 99%
“…However, in spite of the generally used continuous wave pump power of the fundamental frequency (FF) to about 1 W, the peak powers of the generated SHF are usually limited to 10 ¡5 W [17]. Even if it can be increased to 10 ¡2 W in HPW, the corresponding waveguide length to realise this efficiency is 1 mm [18], which is probably too long and not suitable for application in future integrated nanophotonic circuits. The rather small reported efficiencies are due to the relatively small nonlinear susceptibility in crystal, the moderately large nonlinear coupling coefficients between different frequencies and the absorption loss of the plasmonic modes.…”
Section: Introductionmentioning
confidence: 99%